Expanding Nuclear Physics Horizons with the Gamma Factory - Budker, Dmitry; Berengut, Julian C.; Flambaum, Victor V.; Gorchtein, Mikhail; Jin, Junlan; Karbstein, Felix; Krasny, Mieczyslaw Witold; Litvinov, Yuri A.; Pálffy, Adriana; Pascalutsa, Vladimir; Petrenko, Alexey; Surzhykov, Andrey; et al. (Annalen Der Physik, 2022)
The Gamma Factory (GF) is an ambitious proposal, currently explored within the CERN Physics Beyond Colliders program, for a source of photons with energies up to approximate to 400 MeV and photon fluxes (up to approximate to 10(17) photons s(-1)) exceeding those of the currently available gamma sources by orders of magnitude. The high-energy (secondary) photons are produced via resonant scattering of the primary laser photons by highly relativistic partially-stripped ions circulating in the accelerator. The secondary photons are emitted in a narrow cone and the energy of the beam can be monochromatized, down to 10(-3)-10(-6) level, via collimation, at the expense of the photon flux. This paper surveys the new opportunities that may be afforded by the GF in nuclear physics and related fields.
CRIS-Team WoS Importer:2022-03-11